Penambahan Alat Produksi Mesin Perajang Guna Meningkatkan Produktivitas Usaha Mikro Gula Semut - Ananta Kusuma Yoga P.; Oktavima W; Ainurrofiq Ainurrofiq (LOYALITAS: Jurnal Pengabdian Kepada Masyarakat, 2018)
This partnership program aims to provide solutions to the problems being faced by these two partners, namely: 1) Low productivity of ant sugar. Brown sugar must wait to be processed into ants sugar by manually shredded method with a capacity of 7 kg per 2 hours. 2) The resulting brown sugar products are only packaged in plastic bags, there is no brand or product identity color that can be used as a symbol, symbol or product logo, very simple and less attractive or less feasible to sell to consumers.3) On Micro Enterprises " Popular Sugar "products still have no product diversification so that the products produced are only one type. For this reason, coaching programs start from training, guidance and consultation, facilitation of brown sugar chopping machines. So that it is expected that this program will produce the following outputs: 1) Ant sugar chopper machine 2) new / new product packaging. 3) Diversification of new products, namely sugar ants. 4) PIRT certificate